Bridging Skill Gaps: Promoting Creative and Critical Thinking in Graduate Learners Through Alternative Assessment Methods - Cruz, Mary (Global journal of Business and Integral Security, 2024)
In the World Bank Human Capital Index 2022 ranks India 132 out of 191 countries. This is an area of concern as India has the largest youth population, and therefore, they must have the right skill sets to find employment in an agile work environment. The workforce predictions indicate replacing a low- and medium-skilled workforce with smart automation. Given these trends, the Government of India introduced many programs to upskill and re-skill Indian youth, yet the employability of Indian graduates is below 50 percent. Educational reforms are slow-paced when compared to the technological revolutions of the 21st century. This exploratory case study examined the impact of an innovative assessment method, specifically a flip-question paper, to enhance critical and creative thinking amongst graduate learners in a women's college in Bangalore. The survey was conducted with 112 respondents from India and abroad to understand current trends in education and skill gaps. The qualitative exploratory case study was conducted on fifty-four graduate learners over a longitudinal period of six months. The themes of the ACER creative thinking framework were evaluated using the rubric designed to generate the quantitative data. The research aimed to validate that assessments should move from content-driven to more creative forms to improve skills. The concept of differentiated assessment brings out the abilities of each learner. The quantitative data generated after the assessment supported and validated the three hypotheses stated in the study. The study's results confirmed that learners experimenting with their ideas could improve their creative and critical thinking. It can be concluded that this assessment method can be used as a model at the end of a program or the entry-level of employment. It can be concluded that, in an age of rapid automation and smart technologies, educators should focus more on pedagogy and assessment that develop higher-order thinking skills. The findings of this study strongly suggest that alternative assessment methods can serve as a creative tool to bridge skill gaps. The future workspaces dominated by machines will require learners with highly developed skills. Therefore, having these skills marked in transcripts and content knowledge is essential.